Kemampuan Pemecahan Masalah Matematis pada Mata Kuliah Persamaan Diferensial Dilihat dari Pembelajaran Konflik Kognitif yang Terintegrasi dengan Soft Skill - Novi Marliani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2015)
The purpose of this study was to determine differences in cognitive conflict that integrates learning with soft skills to the mathematical problem solving abilities in the course of differential equations. The method used in this research is the method of quasi experiment with comparative analysis that the t test on 40 samples, Samples were taken at random on 6th semester student of mathematics education Universityof of Indraprasta PGRI (UNINDRA) academic year 2013/2014. The results showed differences in cognitive conflict instructional ter integration with soft skills and learning cognitive conflict that is not integrated with the soft skills of the mathematical problem solving abilities in the course of differential equations.